'Não há nada entre nós' : uma (im)possível tradição poética de mulheres no imaginário de Ana Cristina Cesar, Adília Lopes e Patti Smith - Munhoz, Erica Martinelli, 1987- (2023)
Orientador: Cristina Henrique da Costa